Molecular Evidence of SARS-CoV-2 Virus in Dogs and Cats from Grenada - Vanessa Matthew-Belmar; Trevor Noel; Bhumika Sharma; Katherine Yearwood; Paul Fields; Wayne Sylvester; Nandy Noel; Elsa Chitan; Nikita Cudjoe; Veronica Alexander; Christopher Oura; Calum Macpherson; et al. (Veterinary Sciences)
SARS-CoV-2 is a highly contagious virus that infects humans, wildlife, domesticated and farmed animals. An increase in SARS-CoV-2 variants and human–animal interactions could have implications for the global maintenance and perpetuation of the virus. This study aimed to detect SARS-CoV-2 infection in dogs and cats living in households with and without SARS-CoV-2-positive owners by real-time reverse transcription polymerase chain reaction (qRT-PCR) in Grenada. This cross-sectional study was conducted from August 2020 to April 2022 from dogs (139) and cats (22) in households (96) in Grenada. Nasopharyngeal and oropharyngeal swabs were taken from the dogs and cats to detect SARS-CoV-2. qRT-PCR tests were performed targeting the E and RdRP genes, respectively. Notably, 12% (17/139) of dogs and 23% (5/22) of cats tested positive for SARS-CoV-2. The positive animals were found in 17 (18%) households, all with at least one positive individual. No positive cases of pets were detected in households without infected humans. A statistically significant association (p < 0.0001) was observed between humans with SARS-CoV2 and their pets. Phylogenetic tree analysis showed evidence of a relationship between the Grenadian SARS-CoV-2 E gene and other SARS-CoV-2 E gene sequences available in the NCBI database. This study confirmed the concurrent SARS-CoV-2 human/companion animal infection from households in Grenada. Humans and pet animals were positive synchronously; however, the direction of transmission from pets to humans or vice versa remains unknown. This study suggests that pets could play a role in the maintenance, transmission, and prolongation of infection of human-adapted pathogens such as SARS-CoV-2.